¿Qué es un texto? Una teoría pragmática - Bevir, Mark (2006)
“What is a Text? A Pragmatic Theory”. The paper begins by defending a principleof procedural individualism according to which meanings are always subjectiveor inter-subjective.  Texts do not have meanings in themselves, but rather areobjects to which individuals attach various meanings.  Then the paper deploysthis analysis of meaning to address debates about textuality.  It considers thestability of the text: although texts are indeterminate in that future individualsmight attach unforeseen meanings to them, they have determinate content atany given time in that the meanings people have then attached to them arefixed.  And it considers the relationship of textual meaning to authorial meaning:authors and readers alike attach meanings to texts, with confusions arisingwhen philosophers assume that one or other must constitute the meaning ofthe text itself.